Kathleen Hartford y Steven M. Goldstein (comps.), Single sparks, China's rural revolutions, Armonk, Nueva York, M.E. Sharpe Inc., 1989, 216 pp. (Studies of the East Asian Institute Columbia University) - Marisela Connelly (El Colegio de México, A.C., 1990)
.